Fatigue of triply periodic minimal surface (TPMS) metamaterials – a review - Novak, Nejc (Strojniški vestnik, 2025)
A review of the fatigue behavior of triply periodic minimal surface (TPMS) metamaterials with consideration for their fabrication is presented in this paper. The review analyses the most common TPMS geometries used due to their mechanical characteristics. Production methods and the base materials used are presented with the key advantages and drawbacks. Furthermore, the mechanical characteristics of cellular structures with emphasis on TPMS geometries are described. Lastly, the state-of-the-art findings of their fatigue behavior are analyzed and explained. Based on the findings in this article, cellular geometries based on TPMS are superior to conventional cellular structures when comparing their fatigue life. Because of the smooth transitions between struts or surfaces, the stress distribution is much more uniform without stress concentration zones.
Keywords: celične strukture; cellular structures; fatigue behavior; mechanical characterization; mehanska karakterizacija; obnašanje pri utrujanju; production technologies; proizvodne tehnologije; TPMS metamateriali; TPMS metamaterials